طرق التعليم الفعال من خلال كفايات معلمي مادة التفسير - Bunyamin Abdul Rahman (Pascasarjana UIN ANTASARI Banjarmasin, 2019)
Tafsir is an important subject related to understanding the Qur’an. Therefore, the learning process in this subject should use an effective method, so that the learning process is in accordance with the situation of the students. Researchers have found in textbooks and previous research reports that many of the learning methods used in this field are traditional and modern. The researcher is interested in expressing Tafseer's learning method by considering the responsibility of the interpreter. To achieve this, the researchers examined Tafsir's teaching skills, the extent to which the need to have interpreting skills, and those related to personal, social and professional competencies. By using descriptive-analytic methods, this study found that learning of interpretation depends on three basic things: first, the best method used by teachers during interactive learning because it represents the practical side is the Blended Learning Method; second, learning methods that depend on positive and interactive learning outcomes between teachers and students together such as scientific presentations, dialogues, peer education and cooperative education; and third, ways that train students to take responsibility and respect each other, such as problem-solving, project methods, and programmed education methods that have been widely used in the field of education that are effective and consistent with the requirements of this age.من المعلوم أن مادة التفسير هي من إحدى المواد العلمية المهمة التي تتعلق بالقرآن الكريم، حيث إنها تلعب دوراً مهماً ومؤثراً في حياتنا المعاصرة. لذلك فإنه من المستحسن أن نتعلّمها ونعلّمها باستخدام طرق التعليم الفعّال التي قدمها العلماء والتربويون، لكي تتلائم عملية التعليم مع ظروف وأوضاع المتعلمين المعاصرة. وبعد أن تأمل الباحثون في الكتب التربوية والأبحاث العلمية وجدوا أن العديد من طرق التعليم المستخدمة في هذا المجال هي تقليدية وحديثة، ويسعى الباحثون إلى كشف طرق تعليم علم التفسير على امتداد العصور وتنوع الأساليب في التعليم وذلك مع مراعاة الكفاءة التي يتمتع بها معلمو التفسير. ولتحقيق ذلك سوف يقوم الباحثون بتوضيح المقصود بكفاية معلمي مادة التفسير، ومدى ضرورة تحقق الكفاية لدى المعلم، وتصنيف كفاية معلم التفسير المتعلقة بالكفاية الشخصية والاجتماعية والمهنية، ويعتمد تعليم التفسير على ثلاثة أمور أساسية: أولاً الطرق التي يستخدمها المعلم أثناء التعليم التفاعلي مثل ألقاء المحاضرة أو الدرس، وطريقة الأسوة الحسنة وهي تمثل الجانب التطبيقي، وطريقة التعليم المدمج ((Blended Learning Method، وثانياً طرق التعليم التي تعتمد في بناء الدرس بشكل إيجابي وتفاعلي بين المعلم والطلبة معاً للوصول إلى المعرفة المنشودة مثل العروض العلمية، والمناقشة والحوار، وتعليم الأقران والتعليم التعاوني، وثالثاً الطرق التي تهدف إلى تدريب الطلبة على تحمُّل المسؤولية والاحترام المتبادل فيما بينهم مثل طريقة حل المشكلات، وطريقة المشروع، وطريقة التعليم المبرمج التي شاع استخدامها في مجال التعليم الفاعل والمنسجم مع متطلبات هذا العصر. ويستخدم الباحثون في هذا البحث المنهج الوصفي التحليلي.